Colloidal stabilization of calcium carbonate prenucleation clusters with silica - Kellermeier, M.; Gebauer, Denis; Melero-García, E.; Drechsler, M.; Talmon, Y.; Kienle, L.; Cölfen, H.; García-Ruiz, J.; Kunz, W. (Wiley, 2012)
Calcium carbonate precipitation proceeds via a complex multistage scenario involving neutral ion clusters as precursors and amorphous phases as intermediates, which finally transform to crystals. Although the existence of stable clusters in solution prior to nucleation has been demonstrated, the molecular mechanisms by which they precipitate are still obscure. Here, direct insight into the processes that drive the transformation of individual clusters into amorphous nanoparticles is provided by progressive colloidal stabilization of different transient states in silica-containing environments. Nucleation of calcium carbonate in the presence of silica can only take place via cluster aggregation at low pH values. At higher pH, prenucleation clusters become colloidally stabilized and cannot aggregate. Nucleation through structural reorganization within the clusters is not observed under these conditions, indicating that this pathway is blocked by kinetic and/or thermodynamic means. The degree of stabilization against nucleation is found to be sufficient to allow for a dramatic enrichment of solutions with prenucleation clusters and enable their isolation into the dry state. This approach renders direct analyses of the clusters by conventional techniques possible and is thus likely to facilitate deeper insight into the chemistry and structure of these elusive species in the future. Under suitable conditions, added silica binds to ion clusters that exist in CaCO 3 solutions prior to nucleation. The resulting colloidal interactions can be tuned to either fully prevent nucleation and isolate the clusters or allow for their gradual transformation into amorphous nanoparticles. The processes underlying homogeneous nucleation of CaCO 3 become decelerated and can be observed experimentally. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.